2018
DOI: 10.1016/j.joco.2018.02.003
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of amblyopia in Iran: A systematic review

Abstract: PurposeThe aim of this study was to determine the prevalence of amblyopia in the population of Iran.MethodsThis article is a systematic review. A comprehensive search was conducted in PubMed, Scopus, Science Direct, Ovid, Web of Science, SID, Magiran, with appropriate terms. Information related to the sample size and the prevalence of amblyopia was extracted and summarized in tables. Analysis was performed using STATA software.ResultsFrom 551 articles that were originally extracted from the databases, 31 artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…11 The prevalence of amblyopia in Iran was 0.19%-3.9%. 12 The prevalence of amblyopia was found to be 1.1% in young Singaporean-Chinese children.8 A total of 200 students of a school in Lahore, Pakistan, were examined for visual impairments and 3% of them were found to be amblyopic. 13 From different studies it can be observed that prevalence of amblyopia is around 1.09% to 3% of population of any area.…”
Section: Discussionmentioning
confidence: 99%
“…11 The prevalence of amblyopia in Iran was 0.19%-3.9%. 12 The prevalence of amblyopia was found to be 1.1% in young Singaporean-Chinese children.8 A total of 200 students of a school in Lahore, Pakistan, were examined for visual impairments and 3% of them were found to be amblyopic. 13 From different studies it can be observed that prevalence of amblyopia is around 1.09% to 3% of population of any area.…”
Section: Discussionmentioning
confidence: 99%
“…In Arab countries, the prevalence of amblyopia ranged between 1.3-3.9% in Saudi Arabia, in Jordan the prevalence of amblyopia in fi rst and second grades children aged 6 and 7 years was 2.78% [13], in Egypt it was 1.98% [14]. In other countries like Iran and Turkey, prevalence of amblyopia ranged between 0.19% to 3.6% [15,16].…”
Section:  Introductionmentioning
confidence: 99%
“…Amblyopia is one of the common visual disorders caused by abnormalities in the visual system during early childhood with a prevalence of 3%-5% [1][2][3]. It is mainly shown that the best corrected visual acuity is lower than that of the normal age-matched eye without obvious ocular pathology [4].…”
Section: Introductionmentioning
confidence: 99%